Design of control signals for three phase matrix converter on the basis of double Fourier series - Korotyeyev, I.Ye.; Klytta, M. (Технічна електродинаміка, 2014)
A derivation of control signals of three phase matrix converters is based on extension of the space with one to the space with two time variables. The control signals are presented in form of Fourier series with four coefficients. The procedure is based on equating appropriate coefficients corresponding harmonics of double Fourier series and on solving obtained equations.